Para sport translation of the IOC consensus on recording and reporting of data for injury and illness in sport - Derman, W.; Badenhorst, M.; Blauwet, C.; Emery, C. A.; Fagher, K.; Lee, Y.-H.; Kissick, J.; Lexell, J.; Miller, I. S.; Pluim, B. M.; Schwellnus, M.; Steffen, K.; et al. (British Journal of Sports Medicine, 2021)
In 2020, the IOC proposed a universal methodology for the recording and reporting of data for injury and illness in sport. Parasport is played by individuals with impairment, and they have a unique set of considerations not captured by these recommendations. Therefore, the aim of this addendum to IOC consensus statement was to guide the Parasport researcher through the complexities and nuances that should be taken into consideration when collecting, registering, reporting and interpreting data regarding Para athlete health. To develop this translation, experts in the field of Parasports medicine and epidemiology conducted a formal consensus development process, which began in March 2020 with the formation of a consensus group that worked over eight phases, incorporating three virtual consensus meetings to finalise the translation. This translation is consistent with the IOC consensus statement, yet provides more detailed Paraathlete specific definitions and recommendations on study population, specifically, diagnostic and eligible impairment categorisation and recording of adaptive equipment, and defining and classifying health problems in the context of Parasport. Additionally, recommendations and Paraathlete specific examples are described with regards to injury mechanism, mode of onset, injury and illness classification, duration, capturing and reporting exposure and risk. Finally, methods and considerations are provided to cater to the varied needs of athletes with impairment with respect to data collection tools. This harmonisation will allow the science to develop and facilitate a more accurate understanding of injury and illness patterns for tailoring evidence-informed prevention programmes and enabling better planning of medical services for Parasport events.